Daya Terima Puding Jagung dengan Substitusi Kacang Hijau sebagai Alternatif PMT Balita - Hanum, Anida Luthfia; Ani Nuraeni (LPPM Universitas Negeri Jakarta, 2024)
Abstract Nutrition problems in toddlers are still a major health problem in Indonesia, one of which is protein energy deficiency. Efforts in dealing with nutritional problems include supplementary feeding. PMT is given in the form of snacks, namely pudding, by utilising local foods such as corn and mung beans. The aim of the study was to determine the acceptability of corn pudding with mung bean substitution as an alternative PMT for toddlers. Experimental research with a non-factorial complete randomised design (CRD) with three formulas. Determination of acceptability using organoleptic test assessment with hedonic scale. Data were analysed using Kruskal-Wallis non-parametric test with Mann-Whitney follow-up test. Organoleptic test results on colour and taste attributes showed significant differences (p-value <0.05). Based on the exponential comparison method (MPE), F2 was determined as the selected formula. The selected formula pudding product is acceptable to toddlers, based on the level of liking from the results of descriptive percentage analysis of colour, aroma, taste, and texture attributes. The nutritional content per serving was 141 cal of energy, 5.4 g of protein, 3.3 g of fat, and 22.2 g of carbohydrate. Based on the RDA for toddlers, F2 pudding has sufficient energy needs for one meal (10-20% RDA). Keywords: Corn, Mug Bean, Pudding, Toddler PMT